A study in abjection - Leong, Megan Nyuk Leng (2017)
“A Study in Abjection” is a body of work that, I hope, will help myself and others delve into the deep dark world of horror and open our minds to how much of it is in fact a primal instinct. Our minds are hardly our own as our fears and repulsions are decided for us from a young age.